Ligand-induced decarbonylation in diphosphine-ligated palladium acetates [CH3CO2Pd((PR2)2CH2)]+ (R = Me and Ph). Issue 4 (11th December 2017) - Lesslie, Michael; Yang, Yang; Canty, Allan J.; Piacentino, Elettra; Berthias, Francis; Maitre, Philippe; Ryzhov, Victor; O'Hair, Richard A. J.
Abstract : Isotope labelling, IR spectroscopy and DFT calculations reveal a novel ligand-induced decarbonylation reaction. Abstract : A new decarbonylation reaction is observed for [( K 2 -acetate)Pd( K 2 -diphosphine)] + complexes. Gas-phase IR experiments identify the product as [CH3 Pd(OP(Ph2 )CH2 PPh2 )] + . DFT calculations uncovered a plausible mechanism involving O atom abstraction by the diphosphine ligand within the coordination sphere to yield the acetyl complex, [CH3 COPd(OP(Ph2 )CH2 PPh2 )] +, which then undergoes decarbonylation.